Parties to a Contract for the Provision of Rehabilitation Services (Bulletin of Kharkiv National University of Internal Affairs, 2025)
This article is devoted to the characteristics of the parties to a contract for the provision of rehabilitation services. An analysis of the regulatory and legal acts governing legal relations in the field of healthcare and the provision of rehabilitation services is conducted. The work of the scholars researching the legal basis for the provision of rehabilitation assistance in Ukraine, in particular the civil law regulation of this sphere, is considered separately.The parties to the agreement on the provision of rehabilitation services, such as the customer and the contractor, are characterised. The requirements for rehabilitation institutions that can act as contractors under such an agreement are defined. It is emphasised that rehabilitation institutions must have the status of a legal entity and may operate on the basis of private, state or municipal ownership. It is noted that in order to carry out economic activities in the field of medical practice, rehabilitation institutions must obtain an appropriate licence. An important aspect is the availability of qualified rehabilitation specialists on the staff of such institutions.It is clarified that a contract for the provision of rehabilitation assistance may be concluded both by adult individuals and by parents of minors who need rehabilitation assistance. The rights of patients under such an agreement are outlined. It is noted that a patient may also be a foreign citizen who does not permanently reside in Ukraine. It is emphasised that a citizen of Ukraine, on the basis of an agreement on the provision of rehabilitation services, may receive rehabilitation services that are not included in the programme of state guarantees for medical care for the population.It is proposed to amend Article 22 of the Law of Ukraine “On Rehabilitation in the Field of Health Care”, in particular to provide for the right of a patient to conclude an agreement on the provision of rehabilitation services at their own expense. The prospects for further scientific research in the context of the article’s topic are outlined.